Tempting fate [large type] - Green, Jane, 1968- (Wheeler Publishing, 2014)
"Gabby and Elliott have been happily married for eighteen years. They have two teenaged daughters; they have built a life together. So why does forty-three-year-old Gabby feel like she has only three more minutes left of youth? Why do her friends so desperately try to hang on to their attractiveness? And why does she ever even look at the handsome guy--ten years younger--at the other end of the bar one night? Gabby is the last person to have an affair--a physical one, at least. But Matt makes her feel sparkling, fascinating--something she hasn't felt in years. Surely there's no harm in continuing a long-distance friendship? Surely there's no harm in an emotional affair? As Gabby steps ever deeper into the allure of attraction and attention things turn perilous. If she makes one wrong move she could lose everything--and find out what really matters most"--